Living Teologi: Religiusitas dan Hubungan Sosial Pedagang Kaki Lima - Ahmad Amir Aziz (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2020)
The study of religious theology has so far been largely focused on doctrinal beliefs. In reality, the implementation of theological beliefs in today's dynamic life is more needed. This paper intends to discuss the concept of living theology and illustrate its practice at the street vendor community. The data source is taken from the primary literature, works of researchers and articles published in journals. This study found that street vendors have a relatively good religious basis. Their life spirit becomes a positive force in developing their business. Even though they face different social challenges, they can still build social relationships both internally and externally. Living theology that is seen from the lives of street vendors is work ethic, solidarity and social relations based on wisdom values. The characteristics of social theology are important to be developed, as well as an important ingredient in perfecting the living theology framework being developed.